Cultivars of early soybeans subjected to cross-sowing in sowing populations - Kondo Santini, José Mateus; Silveira, Flávio de Oliveira; Buzetti, Salatiér; Perin, Adriano; Furquim, Leonnardo Cruvinel; Coaguila Nunes, Daniel Noe; Lopes Filho, Luiz Cesar (Científica, 2018)
Cross sowing is a little studied technique which may contribute to increase productivity. The objective of this study is to evaluate the effects of cross-sowing on population arrangements of early soybean cultivars with different growth habits. The experiment was completely randomized in a 2 x 3 + 2 factorial design with two cultivars, three cross-sowing populations and two controls (one for each cultivar evaluated, row sowing with 400 thousand plants ha-1). The experiment was conducted in Rio Verde, Goiás (GO) state. We observed that only the cultivar BMX Potência RR differed from the control as for grain yield. The cultivars responded differently to populations. The BMX Potência RR was more productive in the smallest population and the NA 7337 RR had the highest yield in the larger population. Therefore, the growth habit and sowing population have a direct influence on soybean yield in cross-sowing.